2010
DOI: 10.1007/s11998-010-9265-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of core–shell latex particles by emulsion co-polymerization of styrene and butyl acrylate, and evaluation of their pigment properties in emulsion paints

Abstract: A series of core-shell polymeric particles with poly(n-butyl acrylate-co-methacrylic acid-coethylene glycol dimethylacrylate) as core and poly(styrene-co-methyl methacrylate) as shell were prepared by seeded emulsion polymerization. The role of ethylene glycol dimethylacrylate (EGDMA) is to crosslink the core so as to avoid any probability of gel formation and to bind both the core and the shell phase together. The spherical morphology of the core-shell structure was achieved at 60:40 core to shell ratio. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…The model of the polymerization process proposed here is validated through the comparison of the experimental results with the simulations, as pointed out elsewhere (Mendoza et al, 2000) This work deals with the analysis of Mn and Mw of the terpolymer St/MMA/BuA in the presence of n-DDM as chain transfer agent because the study of the terpolymerization of the system St/MMA/BuA and their molecular weights is important in its application as an acrylic resin in industrial paints (Khan et al, 2009;Borthakur et al, 2010) or in nanocomposite coatings (Rong et al, 2011). The terpolymerization model was built up from the theoretical assumptions of the copolymerization of styrene/methyl methacrylate St/MMA system given by Nomura (Nomura and Fujita, 1985).…”
Section: Introductionmentioning
confidence: 84%
“…The model of the polymerization process proposed here is validated through the comparison of the experimental results with the simulations, as pointed out elsewhere (Mendoza et al, 2000) This work deals with the analysis of Mn and Mw of the terpolymer St/MMA/BuA in the presence of n-DDM as chain transfer agent because the study of the terpolymerization of the system St/MMA/BuA and their molecular weights is important in its application as an acrylic resin in industrial paints (Khan et al, 2009;Borthakur et al, 2010) or in nanocomposite coatings (Rong et al, 2011). The terpolymerization model was built up from the theoretical assumptions of the copolymerization of styrene/methyl methacrylate St/MMA system given by Nomura (Nomura and Fujita, 1985).…”
Section: Introductionmentioning
confidence: 84%
“…For example, Borthakur et al prepared a series of core–shell polymeric particles with poly( n ‐butyl acrylate‐ co ‐methacrylic acid‐ co ‐ethylene glycol dimethylacrylate) as the core and poly(styrene‐ co ‐methyl methacrylate) as the shell. They observed that the core–shell morphology was distorted when the concentration of styrene in the shell composition was relatively high, which was attributed to the increase in the viscosity of the polymerization loci . These core–shell latexes can potentially be applied as pigments in emulsion paint and would reduce the amount of TiO 2 used and hence afford a much more cost‐effective method.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the core-shell morphology was distorted when the concentration of styrene in the shell composition was relatively high, which was attributed to the increase in the viscosity of the polymerization loci. 25 These coreshell latexes can potentially be applied as pigments in emulsion paint and would reduce the amount of TiO 2 used and hence afford a much more cost-effective method. Because the hydrophobic monomers have a better lipophilicity, they are more likely to spread into the core phase in which polymerization takes place.…”
Section: Introductionmentioning
confidence: 99%
“…EGDMA was applied to crosslink the copolymer attached on the pigment surface because crosslinking could bind the copolymers on the pigment surface. 20 Furthermore, it is reported that crosslinking polymer/copolymer encapsulated pigment particles own excellent optical property and high stability in emulsion paints and ink jet printing. [21][22][23][24][25] Characteristics of the modified pigment particles such as chemical structure, morphology, particle size as well as the electrophoretic properties were examined by FIIR, TEM and dynamic light scattering, respectively.…”
Section: Introductionmentioning
confidence: 99%